The Influence of Location and Promotion on the Revisit Intention with Satisfaction as a Mediating Variable - Aqila, Rasyiq; Usdek, Dicky Wisnu; Praharjo, Ardik (Jurnal Manajemen Bisnis dan Kewirausahaan, 2024)
This study analyzes the factors affecting the intention to revisit tourist destinations, focusing on location, promotion, and visit satisfaction as mediating variables. The research aims to assess the impact of location and promotion on revisit intention and the mediating role of visit satisfaction in these relationships. A quantitative approach was used with data analyzed via the Macro Hayes method using SPSS 25. The results show that location and promotion both significantly and positively influence the intention to revisit. Additionally, visit satisfaction plays a mediating role in the effects of both location and promotion on revisit intention. These findings offer valuable insights for tourism managers to improve visitor retention through location development, promotional strategies, and enhancing visitor satisfaction.